Development of Gelatin-Based Renewable Packaging with Melaleuca alternifolia Essential Oil for Chicken Breast Preservation - Lima, Rene Pereira de; Carrea, Daniela de Almeida; Garcia, Vitor Augusto dos Santos [UNESP]; Tostes Filgueiras, Cristina; Matta Fakhouri, Farayde; Velasco, José Ignacio (MDPI, 2025)
The aim of this study was to develop gelatin-based films incorporating Melaleuca alternifolia essential oil (MEO) and assess their application on refrigerated chicken breasts. The results showed that MEO exhibited antimicrobial activity against Pseudomonas aeruginosa and Salmonella sp., with inhibition zones of 17 mm and 9 mm, respectively. The minimum inhibitory concentration (MIC) was 10% for P. aeruginosa and 15% for Salmonella sp., demonstrating greater efficacy against P. aeruginosa. The antioxidant analysis using the ABTS method revealed activity of 1309 ± 18.0 μM Trolox/g, while the FRAP method resulted in 446 ± 5.78 μM FeSO4/g. The characterization of the oil by gas chromatography identified major compounds, including 2-carene, γ-terpinene, terpine-4-ol, and α-terpineol. Incorporating the oil into gelatin films resulted in structural changes, such as an increase in thickness (from 0.059 to 0.127 mm) and water vapor permeability. Furthermore, the addition of MEO conferred homogeneous properties to the films with no visible cracks. The incorporation of MEO into gelatin films has shown ABTS antioxidant activity, and FRAP results showed a significant increase with higher MEO concentrations. The packaged samples retained more mass than the control group, which lost about 90% of its weight during storage. Texture analysis revealed only an 8% variation in the Melaleuca-coated samples compared to 19.6% in the control group. These findings indicate that gelatin films containing Melaleuca essential oil effectively improve the shelf life of chicken breasts.
Keywords: antimicrobial packaging; chicken breast preservation; edible films; gelatin-based films; Melaleuca alternifolia; renewable packaging